O jovem frente à velhice e ao envelhecimento: estudo realizado com alunos de 15 a 18 anos de escola pública na região do Itaim Paulista, São Paulo - Oliveira, Sheila Aparecida Pereira de (2009)
This study investigated the vision of the teenagers between 15 e 18 years old, about the old age and aging process. These young people are students, of the third year of the medium teaching, of a public school in Itaim s Region from São Paulo, city zone east of São Paulo. The qualitative approach research was initiated with the bibliographical rising about of the old age, the aging process and the importance education in the young people formation. The study was accomplished at school, in a class with duration of an hour an twenty minutes with twenty seven students, twelve boys and fifteen girls. It sought to know the vision of these young through a dynamic of group, the words and comments done by the teenagers were organized in central themes and separated in categories as: family; diseases, intergeracionais relations; longevity life and expectation; physical appearance and right. The data analysis subjects it rulered in the categories and subjective interpretations the theory light. The results did arise knowledge and questions that corroborate for teenager comprehension the about of the aging process and of the old age, as well as the gap left by the education relatively to the theme in the youth s formation